Ice-templated graphene oxide/chitosan aerogel as an effective adsorbent for sequestration of metanil yellow dye - Lai, Kar Chiew; Hiew, Billie Yan Zhang; Lee, Lai Yee; Gan, Suyin; Thangalazhy-Gopakumar, Suchithra; Chiu, Wee Siong; Khiew, Poi Sim (Elsevier, 2019)
Graphene oxide/chitosan aerogel (GOCA) was prepared by a facile ice-templating technique without using any cross-linking reagent for metanil yellow dye sequestration. The adsorption performance of GOCA was investigated by varying the adsorbent mass, shaking speed, initial pH, contact time, concentration and temperature. The combined effects of adsorption parameters and the optimum conditions for dye removal were determined by response surface methodology. GOCA exhibited large removal efficiencies (91.5–96.4%) over a wide pH range (3–8) and a high adsorption capacity of 430.99 mg/g at 8 mg adsorbent mass, 400 mg/L concentration, 35.19 min contact time and 175 rpm shaking speed. The adsorption equilibrium was best represented by the Langmuir model. GOCA could be easily separated after adsorption and regenerated for re-use in 5 adsorption-desorption cycles thereby maintaining 80% of its adsorption capability. The relatively high adsorption and regeneration capabilities of GOCA render it an attractive adsorbent for treatment of azo dye-polluted water.